Penguatan Badan Usaha Milik Desa (Bumdes) Untuk Pembangunan Berkelanjutan Di Kabupaten Bone Perspektif Maqashid Syariah - Bahri, Syamsul; Hafid, Abd (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to investigate the characteristics of Village Owned Enterprises (BUMDes), analyze the form of bumdes management, and analyze the strategy of strengthening Village Owned Enterprises (BUMDes) in Bone Regency.The analysis unit is a Village Owned Enterprise (BUMDes) with research objects of Bumdes Management, Village Government, and Village Escorts.This research is qualitative research with descriptive research type. Data is collected with interviews and observations.The data was analyzed using qualitative descriptive analysis techniques. Qualitative descriptive technique is qualitative data processing that has been obtained through simple depiction of facts/characteristics.The results of the study that village owned enterprises in Bone District have not found a character that suits local conditions.In running a business still tends to imitate what others have done.BumDes governance has not implemented the principle that should be a handle in conducting activities.The manager still does not have good human resources to innovate, so BUMDes cederung does not experience significant development.bumdes strengthening must be done with a good management approach, improving human resources, strengthening institutions, creating products based on local potential, as well as creating connectivity / business networks.